2000
DOI: 10.1038/sj.gt.3301211
|View full text |Cite
|
Sign up to set email alerts
|

Adeno-associated virus vector-mediated bcl-2 gene transfer into post-ischemic gerbil brain in vivo: prospects for gene therapy of ischemia-induced neuronal death

Abstract: The proto-oncogene bcl-2 is known as an anti-apoptotic gene that confers the ability to block neuronal cell death after transient ischemia. In order to examine whether the bcl-2 gene can be used for protection of ischemic brain injury, we generated adeno-associated virus (AAV) vectors capable of expressing human bcl-2. Replication-defective AAV vectors were found effectively to transfer and express bcl-2 gene in the gerbil hippocampal neurons. Transduction with AAV bcl-2 5 days before forebrain ischemia preven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(41 citation statements)
references
References 38 publications
1
40
0
Order By: Relevance
“…These protective Bcl-2 effects agree with prior reports showing neuroprotection by Bcl-2 against excitotoxins, hypoglycemia and adriamycin in primary cultures derived from a number of brain regions (Jia et al 1996;Lawrence et al 1996;McLaughlin et al 2000;Tamatani et al 2000) and against in vivo models of excitotoxicity, hypoxia-ischemia, ROS generators, or mechanical trauma (Linnik et al 1995;Lawrence et al 1996Lawrence et al , 1997Antonawich et al 1999;Yamada et al 1999;Phillips et al 2000;Shimazaki et al 2000).…”
Section: Glutamate Neurotoxicitysupporting
confidence: 90%
“…These protective Bcl-2 effects agree with prior reports showing neuroprotection by Bcl-2 against excitotoxins, hypoglycemia and adriamycin in primary cultures derived from a number of brain regions (Jia et al 1996;Lawrence et al 1996;McLaughlin et al 2000;Tamatani et al 2000) and against in vivo models of excitotoxicity, hypoxia-ischemia, ROS generators, or mechanical trauma (Linnik et al 1995;Lawrence et al 1996Lawrence et al , 1997Antonawich et al 1999;Yamada et al 1999;Phillips et al 2000;Shimazaki et al 2000).…”
Section: Glutamate Neurotoxicitysupporting
confidence: 90%
“…However, since a variety of promoters, transgenes, ITRs, and brain regions have been used, a direct comparison between species is not possible. [36][37][38][39][40][41] A comparison of AAV2 and AAV5 injection into the rat striatum indicated that AAV5 transduction was less predictable in the direction of spread and in the volume of transduction than AAV2. 41 There have been no studies examining the ability of AAV1 to transduce the brain in the adult of any species.…”
Section: Discussionmentioning
confidence: 99%
“…19,20 These studies, however, used genetically engineered virus vectors such as adenoassociated virus (AAV) 19 or herpes-simplex type I virus Gene Therapy (HSV). 20 Besides the potentially higher biological risk through the transfer of virus genes not necessary for the treatment, with these vectors there is a realistic possibility of permanent integration and expression of transgenic bcl2 in neuronal, glial and endothelial cells in the CNS.…”
Section: Units (Rlu)/mg Protein) Control Nt2 Cells Transfected With mentioning
confidence: 99%